2007
DOI: 10.2337/db06-0881
|View full text |Cite
|
Sign up to set email alerts
|

P2 Promoter Variants of the Hepatocyte Nuclear Factor 4α Gene Are Associated With Type 2 Diabetes in Mexican Americans

Abstract: Common and rare variants of the hepatocyte nuclear factor 4␣ (HNF4A) gene have been associated with type 2 diabetes and related traits in several populations suggesting the involvement of this transcription factor in diabetes pathogenesis. Single nucleotide polymorphisms (SNPs) within a large haplotype block surrounding the alternate P2 promoter, located ϳ45 kb upstream from the coding region, have been investigated in several populations of varying ethnicity with inconsistent results. Additionally, SNPs locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Consistent with our study, Winckler et al and Bagwell et al reported no association of HNF-4α polymorphisms (including rs1884613) with T2D in Scandinavians and Caucasian Americans [11, 18], although several other studies found the significant association with risk of T2D in the Finnish population [16], the Ashkenazi Jews [15], the Mexican Americans [21], and the Norwegians [17]. The opposite findings among different studies may be due to different sample size, environmental factors, and different genetic backgrounds.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our study, Winckler et al and Bagwell et al reported no association of HNF-4α polymorphisms (including rs1884613) with T2D in Scandinavians and Caucasian Americans [11, 18], although several other studies found the significant association with risk of T2D in the Finnish population [16], the Ashkenazi Jews [15], the Mexican Americans [21], and the Norwegians [17]. The opposite findings among different studies may be due to different sample size, environmental factors, and different genetic backgrounds.…”
Section: Discussionsupporting
confidence: 91%
“…However, we observed an association between WFS1 -rs6446482 with T2D in our meta-analysis, and early-onset T2D in our own sample. Wolfram syndrome, characterized by early-onset diabetes, optic atrophy, deafness, and diabetes insipidus is due to mutations of the WFS1 gene [34], which regulates ί cell function in mice [35] and glucagon-like peptide 1-induced insulin secretion in humans [36], suggesting that impaired beta cell function in subjects with the risk allele of WFS1 may promote the onset of T2D as seen in other monogenetic diabetes [37,38]. Thus, it is necessary to replicate this study in a larger sample and sequence this gene for real causative variants.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the MODY1 mutations are presumably on the pancreatic form of HNF4␣ because single-nucleotide polymorphisms in the P2 promoter that drives ␤-cell expression have also been linked to MODY1 (see Ref. 8 and references therein); no such mutations have been identified in the P1 promoter that drives expression in the liver. Consequently, several studies have investigated the role of pancreatic HNF4␣ in diabetes (5,9,10), but much less is known about the role of hepatic HNF4␣ in diabetes.…”
mentioning
confidence: 98%